THE CONSOLIDATION OF LAND WITHIN LAND MASSES SUBJECT TO PARTIAL NATURAL AFFORESTATION - Malashevskyi, Mykola; Malashevska, Olena (Collection of scientific papers «ΛΌГOΣ», 2023)
Urgent issues for Ukraine are low forest area, fragmentation, irrational configuration of the agricultural land tenure as well as the issue of agricultural land natural afforestation [1, 2]. We suggest land consolidation aiming at agricultural and forestry land tenure rationalisation [3].